The Law Enforcement of the Notary Honorary Council against Violations of the Notary Code of Ethics in Cirebon Regency - Susiyanti, Susiyanti (Jurnal Konstatering, 2022)
The aim of this research isTo study and analyze constraints and Solutions in Law Enforcement of the Notary Honorary Council Against Violations of the Notary Code of Ethics in Cirebon Regency. This study uses Sociological Juridical approach method. Based on the research concluded thatThe obstacles faced by the Honorary Council in enforcing the Notary Code of Ethics in Cirebon Regency, the increasing number of Notaries, the Honorary Council only numbering 3 (three) members and is collective in nature so that if someone is unable due to busyness or other constraints, the Honorary Council not carry out their duties optimally, and there are some unscrupulous notaries who want to be examined who have been notified but are not in the office without any reason, with a large working area. The solution carried out by the Honorary Council to prevent and reduce the occurrence of violations of the code of ethics is to provide guidance, supervision, guidance and counseling. Evaluate and improve every violation of the code of ethics committed by a Notary so that the factors that support the occurrence of violations can be minimized and eliminated. And they must have a way to plan strategic steps to be carried out by the Honorary Council to suit the objectives to be achieved.Keywords: Enforcement; Ethics; Notaries.